Cross-sectional associations between vitamin D status and periodontitis in adults in Northern Norway: The Tromsø Study 2015-2016. - Lindholm, Fanny Maria; Jönsson, Birgitta; Brustad, Magritt (BMC Oral Health, 2025)
Vitamin D is involved in the immune system by regulating inflammatory processes. Over the recent decades, there has been an increase in studies investigating the potential influence of vitamin D status on inflammatory diseases and conditions. However, research on the link between vitamin D and periodontitis remains scarce. Hence, we aimed to examine the relationship between serum 25(OH)D levels and periodontitis in an adult population in Northern Norway.